Lighting Solutions to Improve the Valorisation and Fruition of the Parque del Retiro in Madrid. Issue 2 (November 2021) - Carleo, Davide; Gargiulo, Martina; Scorpio, Michelangelo; Ciampi, Giovanni; Corniello, Luigi; Spanodimitriou, Yorgos; Sibilio, Sergio; Chìas, Pilar
Abstract: The lighting design of public spaces, and in particular of green areas, is becoming a growing interest in the contemporary culture, as more and more people are starting to enjoy cities at nighttime. In this study, the lighting design for two main areas of the Parque del Retiro in Madrid (Spain), the Puerta de España and the Paseo de las Estatuas de Reyes, is discussed. Two different lighting scenarios have been designed by means of the software DIALux evo, the first one with the aim of maximise the lighting effect and the second one with the aim to optimize the energy consumption while still allowing for the enhancement of the key characteristics of the two areas. A combined lighting design solution, obtained by using the two scenarios in a weekly schedule, allowed to achieve adequate levels of illumination, an improvement in the feeling of safety in visitors while optimizing energy consumption.